1994
DOI: 10.1002/j.1460-2075.1994.tb06233.x
|View full text |Cite
|
Sign up to set email alerts
|

VIP21/caveolin, glycosphingolipid clusters and the sorting of glycosylphosphatidylinositol-anchored proteins in epithelial cells.

Abstract: We studied the role of the association between glycosylphosphatidylinositol (GPI)‐anchored proteins and glycosphingolipid (GSL) clusters in apical targeting using gD1‐DAF, a GPI‐anchored protein that is differentially sorted by three epithelial cell lines. Differently from MDCK cells, where both gD1‐DAF and glucosylceramide (GlcCer) are sorted to the apical membrane, in MDCK Concanavalin A‐resistant cells (MDCK‐ConAr) gD1‐DAF was mis‐sorted to both surfaces, but GlcCer was still targeted to the apical surface.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
154
3

Year Published

1995
1995
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 160 publications
(173 citation statements)
references
References 65 publications
15
154
3
Order By: Relevance
“…Recently, Stan et al (48) reported that an attempt to use caveolin IgG to enrich for caveolae failed to co-precipitate many of the proteins shown to be associated with caveolae by independent biochemical isolation methods (29, 49 -51), functional assays (3,4,12,52), and electron microscope methods (3,4,10,23,29,31,(53)(54)(55)(56)(57). Several studies (8,14,24,58,59) including this one demonstrate that caveolin is a mobile protein that can come out of membranes and leave behind resident proteins. Consequently, it is difficult to purify caveolae by immunoprecipitating caveolin.…”
Section: Discussionmentioning
confidence: 98%
“…Recently, Stan et al (48) reported that an attempt to use caveolin IgG to enrich for caveolae failed to co-precipitate many of the proteins shown to be associated with caveolae by independent biochemical isolation methods (29, 49 -51), functional assays (3,4,12,52), and electron microscope methods (3,4,10,23,29,31,(53)(54)(55)(56)(57). Several studies (8,14,24,58,59) including this one demonstrate that caveolin is a mobile protein that can come out of membranes and leave behind resident proteins. Consequently, it is difficult to purify caveolae by immunoprecipitating caveolin.…”
Section: Discussionmentioning
confidence: 98%
“…From a functional point of view, the specific association of a given molecular compound with a DRM has been correlated with sorting and, in polarized epithelial cells, with apical-directed membrane transport Ikonen and Simons, 1998;Ikonen, 2001;Simons and van Meer, 1988;Simons and WandingerNess, 1990;Zurzolo et al, 1994). As noted above and elsewhere (de Vries and Hoekstra, 2000), OLGs can also be considered to be polarized, given the remarkable differences in lipid composition of plasma and myelin membrane, the latter being particularly enriched in GSLs, saturated phospholipids and cholesterol, a composition typical of raft-like domains.…”
Section: Rafts and Myelin Formationmentioning
confidence: 99%
“…Particularly in membranes enriched in GSLs and cholesterol, such as in apical membranes, GSL/cholesterol-enriched microdomains or so called 'lipid rafts' may exist and/or arise. These microdomains have been postulated to be involved in signaling and to act as targeting devices in the direct transport of apical proteins from the trans-Golgi network (TGN) to the apical membrane (Brown and Rose, 1992;Hoekstra et al, 2003;Ikonen and Simons, 1998;Ikonen, 2001;Simons and van Meer, 1988;Simons and Wandinger-Ness, 1990;Zurzolo et al, 1994). Given the enrichment of GSLs and cholesterol in myelin, it is tempting to consider that transport and functioning of myelin-specific proteins towards and in the myelin sheath are accomplished in a similar fashion.…”
Section: Introductionmentioning
confidence: 99%
“…Sucrose gradient analysis of TX-100-insoluble material was performed using previously published protocols (40,45). Cells were grown to confluency in 100 mm dishes and labeled overnight with 100 mCi/ml of [ 35 S]-cysteine.…”
Section: Sucrose Density Gradientsmentioning
confidence: 99%